Genotypic potentiality and selection index of ridge gourd (Luffa acutangula L.) - Ahmed, Ayasha; Tarafder, Jahangir Alam; Hoassain, Mohammad Kamal; Alam, Nazmul (Bangladesh Journal of Botany, 2020)
Fifteen ridge gourd genotypes were investigated to select the superior genotypes. The overall analysis reveals that PCV was higher than GCV for all the traits. Significant variation was found among genotypes for the qualitative traits under divergence analysis. The selection index reveals that maximum genetic gain and relative efficiency over selection for yield was obtained for the index I123 based on yield/plant (g), No. of secondary branch, No. of male flower/plant characters. In the presented functions, selection index I1234 and I12345 showed highest relative efficiency over direct selection and genetic gain when all the characters were included to construct the selection index. On the basis of performance, the genotype-3023 was found to be most promising parent in order to develop a commercial ridge gourd variety.